Risk of antibiotics associated with Clostridioides difficile infection: Antibiotic stewardship in action - Andrew T. Dysangco; Tamra M. Pierce; Dawn M. Bravata (Cambridge University Press, 2022)
We examined risk associated with antibiotics used for Clostridioides difficile infection (CDI) at a single site from 2018 through 2020. Overall, 78 patients had nonrecurrent infections. Among inpatient antibiotics, intravenous meropenem had the highest CDI rate (3.56 per 1,000 days of therapy; n = 2 cases). Among outpatient antibiotics, metronidazole had the highest rate (0.071 per 1,000 pills dispensed; n = 3 cases).